Delignification of Elephant Grass for Production of Cellulosic Intermediate. (November 2015) - Minmunin, Jurarut; Limpitipanich, Paiboon; Promwungkwa, Anucha
Abstract: In this work, elephant grass, a species of Napier grass (P. purpureum x P. americanum hybrid) which contains 60.20% cellulose, 23.80% hemicellulose and 8.20% lignin, was tested in laboratory for lignin remover or delignification. Two steps of delignification were combined. Alkali pretreatment was used for determining the best condition of the first delignification. Then, a pretreated material from the best condition was tested with ozonolysis process. Five concentrations of sodium hydroxide (NaOH) with vary from 0.5 to 10.5 wt.% were used for alkali pretreatment. Ozone flow rate of 5 liters per minute for time from 10 to 30 minutes were used. The best condition for the combined process was 5.5 wt.% NaOH solution and 30 minutes of ozone flow. With this condition, 93.78% of lignin was removed and 80.59% of cellulose and 63.57% of solid were recovered comparing with an untreated one. Furthermore, the ratio of lignin to cellulose was dramatically reduced from 0.1362 to 0.0105 which advantages for ethanol production.